Iron Oxide Nanoparticle Delivery of Peptides to the Brain: Reversal of Anxiety during Drug Withdrawal - Vinzant, Nathan; Scholl, Jamie L.; Wu, Chia-Ming; Kindle, Trevor; Koodali, Ranjit; Forster, Gina L. (Frontiers in Neuroscience, 2017)
Targeting neuropeptide systems is important for future advancements in treatment of neurological and psychiatric illnesses. However, many of the peptides and their analogues do not cross the blood-brain barrier (BBB) efficiently. Nanoparticles such as iron oxide can cross the BBB, and here we describe a novel method for the conjugation of a peptide antisauvagine-30 (ASV-30) to iron oxide nanoparticles. Previous research has shown that direct infusion of ASV-30 into the brain reduces anxiety-like behavior in animal models via actions on corticotropin releasing factor type 2 (CRF2) receptors. Therefore, we tested whether iron oxide+ASV-30 complexes cross the BBB of rats and then determined whether iron oxide+ASV-30 nanoparticles are localized with CRF2-expressing neurons. Finally we tested the hypothesis that systemic infusion of iron oxide+ASV-30 can reduce anxiety-like behavior. First we describe the synthesis and demonstrate the stability of iron oxide-peptide nanoparticle complexes. Next, nanoparticles (87.7 μg/kg Fe2O3) with or without ASV-30 (200 μg/kg, ip) were injected into male rats 30 minutes prior to transcardial perfusion and brain fixation for immunohistochemical analysis, or before testing on the elevated plus maze in an amphetamine withdrawal model of anxiety. Systemically administered iron oxide+ASV-30 particles were present in the brain and associated with neurons, including those that express CRF2 receptors, but did not localize with the iron storage protein ferritin. Furthermore, systemic administration of ironoxide+ASV-30 reduced amphetamine withdrawal-induced anxiety without affecting locomotion, suggesting that the anxiolytic effects of ASV-30 were preserved and the bioavailability of ASV-30 was sufficient. The findings demonstrate a novel approach to peptide delivery across the BBB and provide insight as to the neural distribution and efficacy of this nanotechnology.